NHS Scotland's community GP fellowship – a qualitative study of the first year. Issue 6 (2nd November 2018) - Cunningham, David E.; Kane, Lisa; Denney, MeiLing
ABSTRACT: NHS Scotland faces the challenges of an ageing population and a GP recruitment problem. Research has shown that hospital admissions can be reduced if community services can offer enhanced support, in keeping with the Scottish Government's 2020 Vision for healthcare. This study presents the findings of an evaluation of the first year of a three-year community GP fellowship which included working in primary care and secondary care and an educational programme. A grounded theory approach was adopted with data collected from GP fellows and key stakeholders using focus groups and individual interviews. A total of 12 fellows were interviewed at various times in the first year and 22 key stakeholders were interviewed once. The main themes were: aspirations for the fellowship, career choices of recently-qualified GPs, perceptions of primary care and secondary care components, planning and preparation of educational events, the creation of community hubs and identity and status of fellows. The fellowship showed potential for a change in practice and was a good foundation for further collaboration between health care sectors. Physical hubs need to be constructed and resourced to allow fellows to demonstrate a reduction in hospital admissions. More research is needed throughout the lifetime of the fellowship.